Phenology of Major Weeds in Paddy Field of Pokhara, Nepal - Thapa, Chandra Bahadur; KC, Baburam (Himalayan Biodiversity, 2023)
A phenological study of the top 10 major weed species was carried out in Pokhara, On the basis of the important value index (ivi) dominant weeds were: Ageratum conyzoides (14.1), Cynodon dactylon (13.7), Ischaemum rugosum (12.2), Echinochloa crus galli (11.5), Eleocharis atropurpurea (11.0), Bidens pilosa (10.8), Cyperus rotundus (10.0), Cyperus difformis (9.7), Echinochloa colona (8.6) and Murdania nudiflora (8.2). Among them, 8 monocots and 2 dicots belonging to the family Poaceae (4), Cyperaceae (3), Commelimaceae (1) and Asteraceae (2). Monocot species were dominating over dicots.